Clinical indicators for primary cranial CT imaging after mild traumatic brain injury - a retrospective analysis - Sakkas, Andreas; Weiß, Christel; Ebeling, Marcel; Wilde, Frank; Pietzka, Sebastian; Mohammad, Qasim; Thiele, Oliver Christian; Mischkowski, Robert Andreas (Journal of Clinical Medicine, 2023)
The primary aim was to determine the clinical indicators for primary cranial CT imaging in patients after mild traumatic brain injury (mTBI). The secondary aim was to evaluate the need for post-traumatic short-term hospitalization based on primary clinical and CT findings. This was an observational retrospective single-centre study of all the patients who were admitted with mTBI over a five-year period. Demographic and anamnesis data, the clinical and radiological findings, and the outcome were analyzed. An initial cranial CT (CT0) was performed at admission. Repeat CT scans (CT1) were performed after positive CT0 findings and in cases with in-hospital secondary neurological deterioration. Intracranial hemorrhage (ICH) and the patient’s outcome were evaluated using descriptive statistical analysis. A multivariable analysis was performed to find associations between the clinical variables and the pathologic CT findings. A total of 1837 patients (mean age: 70.7 years) with mTBI were included. Acute ICH was detected in 102 patients (5.5%), with a total of 123 intracerebral lesions. In total, 707 (38.4%) patients were admitted for 48 h for in-hospital observation and six patients underwent an immediate neurosurgical intervention. The prevalence of delayed ICH was 0.05%. A Glasgow Coma Scale (GCS) of <15, loss of consciousness, amnesia, seizures, cephalgia, somnolence, dizziness, nausea, and clinical signs of fracture were identified as clinical factors with significantly higher risk of acute ICH. None of the 110 CT1 presented clinical relevance. A GCS of <15, loss of consciousness, amnesia, seizures, cephalgia, somnolence, dizziness, nausea, and clinical signs of cranial fractures should be considered absolute indicators for primary cranial CT imaging. The reported incidence of immediate and delayed traumatic ICH was very low and hospitalization should be decided individually considering both the clinical and CT findings.